Pergolakan agama di Sumatra Barat ; sebuah sumbangan bibliografi - Schrieke, B. J. O. (Bertram Johannes Otto), 1890-1945 (Seri terjemahan karangan-karangan bahasa Belanda, 1973)
Islamic religious disturbances in West Sumatra in the 19th and early 20th century.